Identity Construction and Reversal Conceptual Transfer Among Iranian EFL Learners - Razieh Gholaminejad (Asociación Colombiana de Profesores de Ingles, 2017)
This article draws on a qualitative study which seeks to explore whether Iranian English as a foreign language learners experience any reversal conceptual transfer and whether they construct two identities as a result of learning a foreign language. The findings from the open-ended questionnaires distributed among 65 undergraduates at the University of Isfahan as well as 45 interviews conducted in a private language school reveal that most of the participants feel they have partly experienced reversal conceptual transfer. However, most of them claimed not to have constructed a new foreign language identity in English, while those who did had a more positive attitude towards their English identity.